Exploring compliance of AAOIFI Shariah standard on Ijarah financing: Analysis on the practices of Islamic banks in Malaysia - Shujaat Saleem; Fadillah Mansor (Journal of Risk and Financial Management, 2020)
This paper aims to explore whether the practices of Ijarah financing by Islamic banks in Malaysia are in line with the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) Shariah Standard No: (9) on Ijarah financing. Semi- structured interviews based on open-ended questionnaires were conducted, recorded verbatim, and transcribed for content analysis. Our study revealed flaws in the contemporary practice of Ijarah financing and indicated that it was slightly out of line with the AAOIFI Shariah standard. The study will not only help the Islamic banking industry of Malaysia to reduce, if not eliminate the gap between the practices of Bank Negara Malaysia (BNM) and AAOIFI Shariah standards pertaining to Ijarah financing but also create novel literature due to the fact that, no study has been undertaken to date, which analyzes the practices of Ijarah financing by Malaysian Islamic banks in the light of the AAOIFI Shariah standards.
Keywords: 330; AAOIFI standards; Ijarah financing; Islamic finance; Malaysian Islamic banks